The Effects of Linguistic Devices on Consumer Information Processing and Persuasion: A Language Complexity × Processing Mode Framework. Issue 4 (10th May 2018) - Pogacar, Ruth; Shrum, L. J.; Lowrey, Tina M.
Abstract : People—be they politicians, marketers, job candidates, product reviewers, or romantic interests—often use linguistic devices to persuade others, and there is a sizeable literature that has documented the effects of numerous linguistic devices. However, understanding the implications of these effects is difficult without an organizing framework. To this end, we introduce a Language Complexity × Processing Mode Framework for classifying linguistic devices based on two continuous dimensions: language complexity, ranging from simple to complex, and processing mode, ranging from automatic to controlled. We then use the framework as a basis for reviewing and synthesizing extant research on the effects of the linguistic devices on persuasion, determining the conditions under which the effectiveness of the linguistic devices can be maximized, and reconciling inconsistencies in prior research.